Increased Muscleblind levels by chloroquine treatment improve myotonic dystrophy type 1 phenotypes in in vitro and in vivo models. - Bargiela, A.; Sabater-Arcis, M.; Espinosa-Espinosa, J.; Zulaica, M.; Lopez de Munain, A.; Artero, R. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Myotonic dystrophy type 1 (DM1) is a life-threatening and chronically debilitating neuromuscular disease caused by the expansion of a CTG trinucleotide repeat in the 3' UTR of the DMPK gene. The mutant RNA forms insoluble structures capable of sequestering RNA binding proteins of the Muscleblind-like (MBNL) family, which ultimately leads to phenotypes. In this work, we demonstrate that treatment with the antiautophagic drug chloroquine was sufficient to up-regulate MBNL1 and 2 proteins in Drosophila and mouse (HSALR) models and patient-derived myoblasts. Extra Muscleblind was functional at the molecular level and improved splicing events regulated by MBNLs in all disease models. In vivo, chloroquine restored locomotion, rescued average cross-sectional muscle area, and extended median survival in DM1 flies. In HSALR mice, the drug restored muscular strength and histopathology signs and reduced the grade of myotonia. Taken together, these results offer a means to replenish critically low MBNL levels in DM1.